Investigation on stability of tri-hybrid nanofluids in water-ethylene glycol mixture - A. I., Ramadhan; W. H., Azmi; R., Mamat; K. A., Hamid; Norsakinah, S. (IOP Publishing, 2019)
Nanofluid is a suspension of liquid containing metal or non-metallic nanoparticles of typical size (1-100 nm) dispersed into the base liquid. Hybrid or composite nanofluids is considered an extension of research work for single nanofluids, which can be carried out through a combination of two or more different nanoparticles - either in mixed or dispersed composites in liquids. The objective of this study is to investigate the stability of tri-hybrid nanofluids suspended in Water-Ethylene Glycol (EG) mixture. The tri-hybrid nanofluids were prepared at a volume concentration of 0.05 to 0.3% using the two-step method. Three types of nanoparticles used namely Al2O3, TiO2 and SiO2, and dispersed in a base fluid of water/EG. The investigation on the stability of the hybrid nanofluids in the present study is conducted through UV-Vis, zeta-potential, sedimentation and micrograph observation. The findings from the investigations on the visual stability of sedimentation show that the differences in concentration (0.05, 0.1, 0.2, 0.3%) have been low in day 14. It was found that 10 h sonication time is the most suitable period for sonication to obtain a stable suspension. Comparison of data concentration ratio to sedimentation for single, hybrid and tri-hybrid nanofluids presents tri-hybrid nanofluids remains stable with a concentration ratio of 80%. Zeta potential evaluation conducted for the tri-hybrid nanofluids obtained the value of 25.1 mV in the classification of good stability. It can be concluded that the tri-hybrid nanofluids were successfully prepared and achieved good stability.